Prescribing Pattern of Antibiotics in Paediatric Patients - Kuber, B. Ramya; Avanthi, D.; Vaishnavi, CH. Sri Lalitha; Varma, S. Jigisha (Indian Journal of Pharmacy Practice)
Aim: To collect prescriptions from patients, to assess the prescribing pattern in accordance with the available guidelines. Objective: The main objective is to study the Prescribing pattern of antibiotics in hospital paediatric patients. Method: Non- interventional, prospective observational study of Six month’s duration was undertaken during August – February of 2016-2017. A total number of 300 prescriptions were screened and 140 patients were enrolled for antibiotic study. Patient data relevant to the study was obtained from the prescriptions in direct interview with out- patients under antibiotic therapy and Children under the age of 7. Results: A total of 300 paediatric patients fulfilled the inclusion criteria were enrolled. According to our study there were a total of 110 boys (36.6%) and 190 girls (63.4%). Among 300 patients, the highest number of patients was in the age group less than one year i.e.32% and lowest number was in the age group of 3-5 years i.e.19.3%. In our study, Macrolide antibiotics were found to be widely prescribed. Among all these Macrolide antibiotics- Azithromycin (26.2%) was the leading antibiotic prescribed followed by Cephalosporin’s- Cefixime (24.3%) and the other antibiotics. Most of the antibiotics were administered parenterally for outpatients. Conclusion: Antibiotic prescribing in children is relatively high in Chittoor district of Andhra Pradesh. Prescription of broad-spectrum antibiotics though has increased demonstrably which may result in development of bacterial resistance, however development of guidelines for antibiotic prescription and use of appropriate drugs can result in minimizing the unfavourable use of antibiotics in children.
Keywords: Antibiotics; Paediatrics; Guidelines; Resistance; Prevalence.